2013
DOI: 10.1108/17505931311316734
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reputation and website quality on online consumers' emotion, perceived risk and purchase intention

Abstract: Purpose -This research extends Mehrabian and Russell's Stimulus-Organism-Response model to include both external (i.e. reputation) and internal source of information (i.e. website quality) as stimuli which affect consumers' response systems. The purpose of this paper is to test a more comprehensive model consisting of reputation and website quality (stimuli), cognition and emotion (organism) and purchase intention (response). Design/methodology/approach -In total, 219 usable questionnaires were obtained at a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
368
3
34

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(428 citation statements)
references
References 98 publications
23
368
3
34
Order By: Relevance
“…Through the analysis of the data provided by 219 questionnaires, it is found that web experience has a negative correlation with consumer's perceived risks and a positive correlation with customer's emotional factors. Perceived risks have a negative impact on emotional factors, and perceived risks, emotional factors have a strong impact on purchase intention (Kim, 2013). In Ghalandar's empirical research, he analyzed the relationship between the online purchase intention of the user and the experience of the web, and it shows that the user's understanding and experience of the computer network also affect the purchase intention, the overall web experience has a significant inpact on purchase intention (Ghalandar, 2012).…”
Section: The Relationship Between Web Experience and Purchasing Intenmentioning
confidence: 99%
“…Through the analysis of the data provided by 219 questionnaires, it is found that web experience has a negative correlation with consumer's perceived risks and a positive correlation with customer's emotional factors. Perceived risks have a negative impact on emotional factors, and perceived risks, emotional factors have a strong impact on purchase intention (Kim, 2013). In Ghalandar's empirical research, he analyzed the relationship between the online purchase intention of the user and the experience of the web, and it shows that the user's understanding and experience of the computer network also affect the purchase intention, the overall web experience has a significant inpact on purchase intention (Ghalandar, 2012).…”
Section: The Relationship Between Web Experience and Purchasing Intenmentioning
confidence: 99%
“…Similarly for e-servicescape, the stimuli are the website environment and service factors. Kim and Lennon (2013) investigated reputation and website quality as the stimuli, cognition and emotion as the organism, and purchase intentions as the response and found that reputation influenced individuals' emotions. The SOR model has also been used to research website characteristics, consumers' emotional responses, and buying behavior (Mummalaneni 2005).…”
Section: Stimulus-organism-response (Sor) Theorymentioning
confidence: 99%
“…First, a firm's reputation is an external information source that acts on the consumer responses and future intentions (Kim and Lennon, 2013). It shows the reliability of the firm's commitments, makes consumers recognize its work, and it is critical in the development of trust in the initial stages and maintaining it in the future (Kim and Prabhakar, 2004).…”
Section: Determinants Of Trust and Satisfactionmentioning
confidence: 99%
“…In the mobile context, research stressed the importance of reputation as it relates to consumer trust (Casaló et al, 2007), which is considered the most important factor in its development (Davis, Sajtos, and Chaudhri, 2011). In the case of clothing, consumers tend to have more positive emotional experiences with those companies with the best reputation, in addition to seeing a reduced perceived risk on the web (Kim and Lennon, 2013;Kim, Yang, and Kim, 2013).…”
Section: Determinants Of Trust and Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation